2016
DOI: 10.1007/s11695-016-2127-y
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Impedance Manometry after Sleeve Gastrectomy: Increased Intragastric Pressure and Reflux are Frequent Events

Abstract: SG significantly modified esophagogastric motility. IIGP is frequent, not correlated to symptoms, and should be regarded as a HRIM marker of SG. Impedance reflux episodes were also frequent, associated with GER symptoms and esophageal dysmotility. HRIM may thus have a clinical impact on the management of patients with upper GI symptoms after SG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(53 citation statements)
references
References 32 publications
1
47
0
5
Order By: Relevance
“…However, in the current study, there was no increase in intragastric pressure. Some studies have reported a difference in pressure [26,27]. Although the reason has not been fully explained, it has been suggested that with a resection made close to the antrum (< 3 cm), the rate of stomach evacuation is increased, and there is stomach drainage without making any change to the intragastric pressure [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current study, there was no increase in intragastric pressure. Some studies have reported a difference in pressure [26,27]. Although the reason has not been fully explained, it has been suggested that with a resection made close to the antrum (< 3 cm), the rate of stomach evacuation is increased, and there is stomach drainage without making any change to the intragastric pressure [28].…”
Section: Discussionmentioning
confidence: 99%
“…Rebecchi et al 17 , no encontraron cambios en EEI y Del Genio et al 8 , con la manometría de alta resolución mostró que la función del EEI no sufría cambios, pero mostró peristalsis ineficaz y mal vaciamiento esofágico, pero sorprendentemente, estos mismos autores informaron incompetencia cardial o hernia hiatal asociada con la presencia de síntomas de reflujo con índice de síntomas aumentado, esofagitis endoscópica y ERGE di novo en el 5,4% de los pacientes. Por el contrario, otros autores 14,[18][19][20][21][22] , han demostrado un efecto nocivo sobre la presión del EEI, lo que indica una disminución de la presión del LES. Burgerhart 14 observó una disminución en la presión de reposo LES de 18,3 ± 9,2 a 11,0 ± 7,0 mmHg (p = 0,02) medida por manometría de alta resolución.…”
Section: Estudios Manométricos Y Monitoreo De Ph áCido Intraesofágicounclassified
“…En realidad, la manometría de alta resolución puede proporcionar información precisa sobre la morfología del EEI después de la manga y demostrar que la separación creciente entre EEI y crura diafragmática puede causar un aumento gradual y significativo en el reflujo [22][23][24][25] .…”
Section: Estudios Manométricos Y Monitoreo De Ph áCido Intraesofágicounclassified
“…Thus, a low-pressure gastric conduit is constructed [19], unlike the high-pressure conduit of the LSG [20].…”
Section: Creation Of the Pouchmentioning
confidence: 99%